Land degradation and the Sustainable Development Goals: Threats and potential remedies. - Vlek, Paul L.G.; Tamene, Lulseged D.; Martius, Christopher; Lamers, John P.A.; Drechsel, Pay; Ziadat, Feras M.; Le, Quang Bao; Mirzabaev, Alisher; Nkonya, Ephraim M.; Lynden, Godert van; Whitbread, Anthony M.; Akhtar-Schuster, Mariam; et al. (2017)
The concern for the well-being of land is often directly related to one's proximity to the land, be it physically, economically or culturally. Land is more precious if one's livelihood depend on it immediately than if one is merely a visitor. Land is valued differently if it is the base of one's power or wealth than if one's community is in need of its integrity and depends on the ecosystem services (ESS) that it provides. To some extent, this may explain the great challenge UNCCD has experienced in mustering international support for its mandate. De facto, the degradation of land has long been seen as a local concern, and in contrast with climate water pollution, not one that would affect populations beyond the location where the problem originated. The arrival of environmental migrants far from the affected regions is contributing to a change of vision and increased urgency to counter land degradation. With the international community taking note of this paradigm shift, the SDGs have addressed the issue head on in SDG 15 and in formulating an objective of land degradation neutrality (LDN). However, development has a number of aspects that may not easily be reconciled with sustainable development. Urbanization, alleviating pressure on land resources, involves the loss of (often) prime land and ESS saving urbanization concepts such as near-natural urbanization and waste recycling are in their infancy. Globalization distributes jobs and wealth on a large scale but also moves large amounts of nutrients around the world often to the detriment of the delivering and the receiving regions. On a local scale, SDGs themselves may be difficult to reconcile as the pursuit of one SDG may be at the expense of another. Many of these dilemmas are grounded in the multiple ecosystem services that are derived from land and their complex interaction and the different scales at which stakeholders are demanding these services. Research on these complex socio-ecological systems is rapidly evolving with the help of modern tools including systems modelling, big data and geo-observation equipment, but given the SDG aspirations for 2030, the scientific community is engaged in a game of catch up. Society as a whole is conflicted as it is polarized when it comes to acknowledging the seriousness and complexity of the problems of sustainable development and its associated costs and benefits. Land degradation is a complicating factor in reaching many of the SDGs, not only SDG 15 but many of the others such as the elimination of hunger, the provision of biodiversity, clean water and renewable energy, climate change mitigation and sustainable urban environments that all depend on healthy land resources. Through its effect on individual SDGs, land degradation can have systemic effects on other, both land and not land-related SDGs, e.g. land degradation that reduces food security in marginal areas contributes to increasing global and national inequalities. Although the phenomenology of land degradation is well known, knowledge on the extent and cost of it is patchy and far from precise. Whatever the approach or methodology used to calculate the costs of land degradation, these costs are very high. There is an urgent need to develop tools and databases that will take stock of the state of our land, which then can serve as a baseline against which LDN can be monitored. Despite the uncertainties, it is consensus that the cost of land degradation is enormous and if not arrested will be a serious drain on the world economy, in particular on the weaker economies of the world. In the quest against land degradation, the scale of engagement is paramount. The scope of a traditional custodian of our land, the farmer, in combating land degradation is often limited to the benefits he would reap. Many of the measures that can combat land degradation involve investments and for the farmer to do his share he will have to be secure in the rights to or use of the land and he has to have the resources to make adjustments in the management of his land. Climate-smart agriculture practices and conservation agriculture are management options for sustainable agriculture but their effect is limited in the context of the SDGs if they are not brought to scale and tied in with a sustainable land and landscape effort. Only at this scale the public benefits will become obvious. This requires collective action, based on stakeholder involvement and the latest science and be based on principle of development, equity and social justice. There is an increasing awareness of the need for integrated management of land and water resources (ILWM) at the watershed and landscape level. Land management needs to spare water and water management needs to optimize ESS from land while satisfying the needs for water in multiple sectors. Keeping in mind the many purposes of these resources, ILWM should derive the optimal mix of ESS without diminishing the resource base. Finding win-win options or the best trade-offs of land use and management based on resource endowment and stakeholder needs is a novel endeavor with which the scientific community is slowly coming to terms. At the community level the need to manage landscapes is increasingly recognized. Integrated landscape management to allocate land to different uses in order to retain or regain the integrity of the landscape. Policymakers are recognizing the need for action and are aiming to provide the institutional environment, markets and (dis-) incentives to support communities that are ready to act. Given the complexity of the socio-ecological systems, the scientific solutions and recommendations are often unknown or untested. Aware of the urgency of action, many communities and policymakers are experimenting with potential solutions of their own. The scientific community is following these experiments and documenting them. From the experiments of the past decades, we can draw a number of lessons. Agricultural research has to expand its focus from field and plot research to landscape research and in the process should look at the cost of production by internalizing environmental cost. In some situations, the public cost of agriculture in marginal environments outweighs the private gains even with the best technologies in place. Land-use and city planners will increasingly have to address the cost of occupying productive agricultural land or the conversion of natural habitats. There is a great need to close nutrient cycles and improve the efficiency of external inputs. Landscape designs and urban planning should aim for the conservation of resources, the restoration of biodiversity and the optimal delivery of ESS. Land degradation issues are local in nature as the problems, the social context and the stakeholder communities are rarely the same. As a result, solutions to land degradation can rarely be generalized. As a result, LDN will be met only through a multitude of efforts, tailored to the conditions of the landscape, community and national interests in a process of negotiations at each level. If land degradation is not held in check, the grounds on which the SDGs are build may be slipping beyond reach.